ijps 2019
DOI: 10.36468/pharmaceutical-sciences.590
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional, Phytochemical and Antioxidant Analysis of Bee Bread from Different Regions of Malaysia

Abstract: Bee bread samples of stingless bee (Heterotrigona itama) collected from Kelantan (east coast), Selangor (central) and Perak (northern) regions of Malaysia were subjected to nutritional analysis using standard hydrolysis and oxidation methods. Phytochemical screening was carried out on aqueous and ethanol extracts of bee bread. Total phenolic and flavonoid contents, free radical scavenging activity and ferric reducing activity of the extracts were also assessed. All samples had essential and non-essential amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…However, it is suggested to further quantify these identified phenolic compounds in future study. In addition, previous studies have reported that bee bread also contains other compounds that have antioxidant properties, such as amino acids, vitamins, and minerals [9,37,38]. As reported in our previous study, the bee bread used in the present study consists of carbohydrate (59.55%), protein (18.37%), and fat (4.51%) [38].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…However, it is suggested to further quantify these identified phenolic compounds in future study. In addition, previous studies have reported that bee bread also contains other compounds that have antioxidant properties, such as amino acids, vitamins, and minerals [9,37,38]. As reported in our previous study, the bee bread used in the present study consists of carbohydrate (59.55%), protein (18.37%), and fat (4.51%) [38].…”
Section: Discussionmentioning
confidence: 55%
“…In addition, previous studies have reported that bee bread also contains other compounds that have antioxidant properties, such as amino acids, vitamins, and minerals [9,37,38]. As reported in our previous study, the bee bread used in the present study consists of carbohydrate (59.55%), protein (18.37%), and fat (4.51%) [38]. Hence, the antioxidant effect of bee bread found in the present study could also partly due to the interaction among these compounds, which needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ethanolic extract and aqueous extract of Heterotrigona itama bee bread yielded different amounts of polyphenols. Ethanolic extracts were found to have higher TPC (21.32–22.54 mg GAE/g) and TFC (16.48–26.57 mg QE/g) than aqueous extract [ 78 ]. When comparing between ethanol and methanol, both solvents showed similar efficiency in extracting phenolic compounds from Australian Austroplebeia spp.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…Figure 4 shows the chemical structures of the bioactive compounds. In general, kaempferol, isorhamnetin, and quercetin were the most frequently detected compounds in bee bread of stingless bee [ 9 , 29 , 78 , 101 ]. These molecules are also widely found in bee pollen of Apis spp.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…Studies on flavonoid content of food incorporated with bee bread or bee pollen are scarce even though the commonly found phenolic compounds in bee bread were flavonoids such as kaempferol, quercetin, and luteolin [29]. According to Othman et al [30], TFC in H. itama BBE was in the range of 16.71 to 26.57 mg QE/g extract. Nevertheless, in this study, the TFC range for BBE fish sausages was incredibly low (1.99 to 8.05 mg rutin/sample).…”
Section: Total Phenolic Content and Total Flavonoid Contentmentioning
confidence: 99%